Centro de bienestar canino “dejando huellas” en la ciudad de Bucaramanga (2023)
The architectural project developed that has the name Centro de canine wellness "dejando huellas" is located in the city of Bucaramanga, more specifically in commune 11 in the Los Conquistadores neighborhood, based on a general analysis carried out in the city, where it was sought find the best location for the project, taking into account multiple aspects such as the terrain, the dimensions, the centrality, the percentage of canines, among others, with the aim of giving a real viability to the service of the citizenry.